2018
DOI: 10.1177/1687814018799604
|View full text |Cite
|
Sign up to set email alerts
|

Study of membrane restrictors in hydrostatic bearing

Abstract: Hydrostatic guides or bearings are very important crucial components in precision mechanical system. First, the article selects the structural parameters of the standard design film restrictor with regard to hydrostatic bearing. Moreover, using COMSOL, the article performs the fluid-structure interaction analysis of the diaphragm to obtain pressure and stress field distribution, and the deformation of diaphragm in membrane restrictors. Then, fluid resistance and other related properties of the membrane restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…To compensate for the bearing stiffness, Lentini et al (2020) optimized the orifice of the aerostatic pad and develop a flow feedback model using a diaphragm valve. Chen et al (2018) designed a hydrostatic bearing with the elastic diaphragm and carried out a fluid-solid coupling analysis. This bearing primarily compensates the flow through the pressure feedback effect of the throttle to improve the load capacity.…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
“…To compensate for the bearing stiffness, Lentini et al (2020) optimized the orifice of the aerostatic pad and develop a flow feedback model using a diaphragm valve. Chen et al (2018) designed a hydrostatic bearing with the elastic diaphragm and carried out a fluid-solid coupling analysis. This bearing primarily compensates the flow through the pressure feedback effect of the throttle to improve the load capacity.…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
“…The restrictor plays an important role in achieving high stiffness, stability, and control. Many types of such devices have been proposed to improve the bearing performance, such as ori ce [9,10], membrane members [11], or feedback systems [12]. The lubricant supply is necessary for proper function while moving or until the required sliding speed is reached, in the case of hybrid bearings, for the hydrodynamic effect to occur and carry the load.…”
Section: Introductionmentioning
confidence: 99%
“…Bassani [12], Chang [13] and Pan [14] also worked on the parameter design and performance analysis off membrane-type restrictor. Chen et al [15] performed a fluid-structure interaction analysis of the diaphragm to more acurrately model the behavior of membrane restrictors.…”
Section: Introductionmentioning
confidence: 99%
“…K * mi > 1. 33 Theoretically, infinite stiffness for the single pad hydrostatic bearing can be achieved by using a membrane restrictor with a K * mi of 4/3 and α mia of 1/4 when loading appeared at the β c of 1/3 [15]. However, it was also found that the stiffness of the system was very low when the loading was small.…”
mentioning
confidence: 99%